An assessment of the effect of participation on sustainable development in a rural electrification project : a case study of the Ipari-Efugo project - Itodo, Anthony Onoja (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2008.